Manajemen Pendidikan Karakter dalam Mewujudkan Peserta Didik yang Berakhlakul Karimah di Madrasah Ibtidaiyah Negeri 04 Banjarnegara - Asih Suprapti (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2021)
This research is based on the importance of student character problems which are still not satisfactory. In this regard, this study aims to determine the management of character education in realizing students who have good morals at MIN 04 Banjarnegara. This research is a qualitative research. Collecting data using interviews, observation, and documentation. The validity of the data using triangulation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. This research resulted in five conclusions: (1) Character education planning is carried out by instilling values ​​and morality in students. These values ​​and morality are adapted to the vision and mission of the madrasa. The character values ​​that are instilled include: religious, honesty, hard work, smart, and caring. (2) The organization of character education has gone well, where the teachers serve as role models for students in madrasas. These values ​​and morality are carried out in various ways according to the style of each teacher. (3) Directing character education includes activities to improve teacher-student relationships, provide opportunities for students to express opinions, and provide motivation to students. (4) Control of character education is carried out by providing skills to students for the development of moral values ​​and literacy. These skills include: critical thinking skills, creative thinking skills, clear communication skills, listening skills, and good moral habits.